Structure of a mutant β toxin from Staphylococcus aureus reveals domain swapping and conformational flexibility - Kruse, Andrew C. (International Union of Crystallography, 2011)
The 3.35 Å resolution crystal structure of a mutant form of the staphylococcal sphingomyelinase β toxin in which a conserved hydrophobic β-hairpin has been deleted is reported. It is shown that this mutation induces domain swapping of a C-terminal β-strand, leading to the formation of dimers linked by a conformationally flexible hinge region. Eight dimers are seen in the asymmetric unit, exhibiting a broad spectrum of conformations trapped in place by intermolecular contacts within the crystal lattice. Furthermore, the 16 monomers within each asymmetric unit exhibit a remarkable heterogeneity in thermal factors, which can be accounted for by the varying degrees to which each monomer interacts with other molecules in the crystal. This structure provides a unique example of the challenges associated with crystallographic study of flexible proteins.